2011
DOI: 10.4314/pamj.v10i0.72223
|View full text |Cite
|
Sign up to set email alerts
|

Controlling sickle cell disease in Ghana ethics and options

Abstract: Sickle Cell Disease (SCD) is a significant public health burden in Ghana. Recent studies indicate that 2% of Ghanaian newborns are affected by SCD; one in three Ghanaians has the hemoglobin S and/or C gene. As a means of controlling the disease, some authorities have recommended prenatal diagnosis (PND) and selective abortion. In the current era, SCD has a good prognosis and fairly reasonable quality of life. Advances in bone marrow transplantation have shown the disease is curable in selected patients. PND an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…The analysis showed most caregivers believed NCDs had negatively affected child's physical growth and school attendance and had caused caregivers/ parents to spend so much money. This finding conforms to earlier research on the social and economic burden of NCDs on families in Ghana 20,24 . Diabetes, especially, type 2 diabetes in the young, is also an increasing problem with potentially serious outcomes 25 .The increasing prevalence of pediatric type 2 diabetes coincides with increasing obesity in children 26 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The analysis showed most caregivers believed NCDs had negatively affected child's physical growth and school attendance and had caused caregivers/ parents to spend so much money. This finding conforms to earlier research on the social and economic burden of NCDs on families in Ghana 20,24 . Diabetes, especially, type 2 diabetes in the young, is also an increasing problem with potentially serious outcomes 25 .The increasing prevalence of pediatric type 2 diabetes coincides with increasing obesity in children 26 .…”
Section: Discussionsupporting
confidence: 80%
“…Sickle cell disease has long been identified to afflict children in Ghana and has severe educational and developmental challenges as well as economic and social challenges for the family 20,24 . The analysis showed most caregivers believed NCDs had negatively affected child's physical growth and school attendance and had caused caregivers/ parents to spend so much money.…”
Section: Discussionmentioning
confidence: 99%
“…This is much lower than the reported national prevalence of 30% and the report of Edwin and others. 5,11 Most participants (87.4%) knew their trait status. This is in contrast to the study of Treadwell et al, where only 16% knew their trait status, but very similar to the finding of Boyd and others, where 89% of African-American women aged 18-30 years were aware of their trait status.…”
Section: Discussionmentioning
confidence: 99%
“…Natural selection factors are the main reason for the high frequencies of the disease in tropical countries and in countries to which large populations have migrated from these regions. The World Health Organization reported that ~2% of newborns in Nigeria and Ghana were affected by sickle cell anemia, with a total of 150,000 affected children born each year in Nigeria alone (5,6). The frequency of SCD ranges from 10 to 40% across equatorial Africa, decreasing to 1-2% at the North African coast and <1% in South Africa (5).…”
Section: Introductionmentioning
confidence: 99%